ANALYSIS OF MATHEMATICS PROBLEM SOLVING DIFFICULTY ON MAIN MATTER OF OPPORTUNITY - Shania Laras Minerva; Mohammad Shaefur Rokhman; Ahmadi Ahmadi (Universitas Negeri Makassar, 2022)
This study aims to describe and analyze the difficulty of solving mathematical problems on the material of opportunity when viewed from the learning style of students. This research is a type of qualitative research. The method used in this study is a learning style questionnaire, mathematical problem-solving ability tests, interviews and, documentation. Based on the results of research and discussion, it was concluded that Students with visual learning styles had difficulties at the stage of understanding the problem, the stage of determining the completion plan, and the stage of re-examining the solution; Learners with auditory learning styles have difficulties at the stage of understanding the problem, the stage of determining the completion plan, and the stage of re-examining the settlement;Students with a kinesthetic learning style have difficulties at the stage of understanding the problem, determining a settlement plan, implementing a settlement plan, and re-examining the solution.